READING CULTURE – THE BASIS OF THE DEVELOPMENT OF SCIENCE - Abdusalom Umarov (International Journal of Literature and Language Studies, 2026)
Abstract. This article reveals through some historical examples how the development of reading culture in society, first of all, causes the development of science and technology, leading to general socio-economic progress.